Fibre cladding interferometers and Bragg gratings made via plane by plane femtosecond laser inscription - Theodosiou, Antreas; Ioannou, Andreas; Kalli, Kyriacos (My University, 2019)
We present an extremely flexible femtosecond (fs) laser inscription method, applicable to the development of critical filtering and wave-guiding components in optical fibres. We inscribe in-fibre devices, such as cladding waveguides (CWGs), cladding Mach-Zehnder interferometers (MZIs) and embedded waveguide Bragg gratings (WBGs) using the same key femtosecond laser parameters, via an "inscribe and step", plane-by-plane (Pl-by-Pl) approach, applied as necessary on two orthogonal axes. This leads to femtosecond laser-inscribed cladding waveguides and ultra-compact MZIs that can support functional, integrated fibre Bragg gratings (FBGs); the unique sensing characteristics of the filters are maintained and provide complementary measurand information. The flexibility and control in waveguide/grating fabrication leads to sensing device customization, e.g.Tailored bend sensing. We characterize CWG-WBG devices for their bend response, whereas the MZI-WBG is exposed to temperature and humidity excursions, confirming the unique sensor responses are maintained for this compact, compound sensor. The MZI exhibits response to external refractive index, a large, negative wavelength response with temperature and high sensitivity to humidity, whereas the MZI-located WBG displays a similar sensitivity to conventional core-based Bragg grating sensors to temperature and no response to relative humidity. We consider that this research is an important step in developing compact, smart optical fibre sensors.
Keywords: Bragg gratings; Femtosecond laser inscription; Fibre waveguides; Optical fibre sensing